Mitochondrial dysfunction in down syndrome: molecular mechanisms and therapeutic targets - Antonella Izzo; Nunzia Mollo; Maria Nitti; Simona Paladino; Gaetano Calì; Rita Genesio; Ferdinando Bonfiglio; Rita Cicatiello; Maria Barbato; Viviana Sarnataro; Anna Conti; Lucio Nitsch (BMC, 2018)
Abstract Trisomy of chromosome 21 (TS21) is the most common autosomal aneuploidy compatible with postnatal survival with a prevalence of 1 in 700 newborns. Its phenotype is highly complex with constant features, such as mental retardation, dysmorphic traits and hypotonia, and variable features including heart defects, susceptibility to Alzheimer's disease (AD), type 2 diabetes, obesity and immune disorders. Overexpression of genes on chromosome-21 (Hsa21) is responsible for the pathogenesis of Down syndrome (DS) phenotypic features either in a direct or in an indirect manner since many Hsa21 genes can affect the expression of other genes mapping to different chromosomes. Many of these genes are involved in mitochondrial function and energy conversion, and play a central role in the mitochondrial dysfunction and chronic oxidative stress, consistently observed in DS subjects. Recent studies highlight the deep interconnections between mitochondrial dysfunction and DS phenotype. In this short review we first provide a basic overview of mitochondrial phenotype in DS cells and tissues. We then discuss how specific Hsa21 genes may be involved in determining the disruption of mitochondrial DS phenotype and biogenesis. Finally we briefly focus on drugs that affect mitochondrial function and mitochondrial network suggesting possible therapeutic approaches to improve and/or prevent some aspects of the DS phenotype.